Effectiveness of The Project Management in Libraries: A Systematic Review - Özdamlı, Fezile; Sultan, Sualeha; Karanfiller, Tolgay (Information World, 2023)
Technology is used to keep track of things and timing and make the best decision on the information available. Project Management (PM) has to offer through its various software and technical tools. PM software has always been compared to the traditional ways of libraries. If a library has always been compared to its traditional ways of doing projects, PM brings systematic strategies to the planned project of libraries from beginning to end. The main objective of this research is to find a systematic literature review on the software of PM, the -advantages of using PM in libraries, and the challenges faced by the libraries using PM. This research used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to illustrate the systematic literature review. The terms “Project Management” and (“library” OR “libraries”) were applied to the advanced research of the five databases: Ebscohost, Emerald, Scopus, WOS, and ScienceDirect were selected databases to ensure relevant studies were captured. The main finding from the research is that using Project Management software in libraries has many advantages, such as clarity of planning and a good understanding of technical tools and software, despite many challenges. It provides end-to-end planning and can be adapted to frequent changes to increase productivity and success. In addition, unlike other studies, this study indicates the missing gap in the literature, and it is hoped that it will guide the researchers.
Keywords: Project Management; library; software; advantages; challenges